2015
DOI: 10.5812/numonthly.28526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hemodialysis on Lipid Peroxidation, Enzymatic and Non-Enzymatic Antioxidant Capacity in Chronic Renal Failure Patients

Abstract: Background:Free radical induced damages are thought to be involved in chronic kidney disease (CKD), especially in patients who are on hemodialysis (HD) for prolonged periods. Hemodialysis can influence multiple biochemical factors, several of which are useful, although the rest can be harmful and increase the severity of disease.Objectives:The purpose of this study was to evaluate the effect of the HD membrane polysulfone on oxidative stress markers, by measuring the level of lipid peroxidation and total antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
(31 reference statements)
3
21
2
1
Order By: Relevance
“…Increased oxidative stress is a critical accompaniment in HD patients, since they live with uremic toxins, are regularly exposed to dialyzer membranes and receive a different rate of dialysis blood flow during HD treatment . A strategy may very well be warranted for HD patients to either decrease their oxidative stress or increase their antioxidant capacities in order to keep the balance of oxidative stress and antioxidant capacities.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Increased oxidative stress is a critical accompaniment in HD patients, since they live with uremic toxins, are regularly exposed to dialyzer membranes and receive a different rate of dialysis blood flow during HD treatment . A strategy may very well be warranted for HD patients to either decrease their oxidative stress or increase their antioxidant capacities in order to keep the balance of oxidative stress and antioxidant capacities.…”
Section: Discussioncontrasting
confidence: 62%
“…The progression of chronic kidney disease (CKD) to the advanced stage generates an excessive amount of reactive oxygen species, which contributes to the eventual development of the end stage of renal disease, such as what occurs in haemodialysis (HD) patients, who are in a pro‐oxidant state . Although malondialdehyde (MDA) is a water‐soluble product of lipid peroxidation with a low molecular weight, and can be theoretically removed through HD treatment, increased lipid peroxidation after HD treatment has been reported in previous studies . If patients receiving HD treatment are potentially at increased oxidative stress, adequate antioxidant capacities to prevent cells from sustaining oxidative damage are of paramount importance for HD patients.…”
mentioning
confidence: 99%
“…Previous studies have revealed a significant imbalance of pro-oxidants and antioxidants in patients with CKD and diabetes [15,16,19,24,25]. It is also well known that bilirubin shows an antioxidant capacity, as in neonatal patients with increased bilirubin levels [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The level of TAC was estimated in all these 30 samples. Low TAC was also provided from chronic kidney failure patients after a renal replacement treatment session [16].…”
Section: Patientsmentioning
confidence: 99%
“…The relationship between cancer and free radicals has been studied (3,4). Antioxidant compounds have been shown to slow down the development of chemically induced tumors (5)(6)(7)(8). It has been estimated that the most of human cancer cases are due to environmental factors and would be preventable if the main risks could be identified (9,10).…”
Section: Introductionmentioning
confidence: 99%